Research, innovation and technological performance in Germany - EFI Report 2013 - EFI - Commission of Experts for Research; Innovation (Commission of Experts for Research and Innovation (EFI), 2013)
In their Annual Report 2013, the Commission of Experts for Research and Innovation presents current analyses, assessments and recommendations on designing the German research and innovation system. With regard to its R&I policies, Germany has made substantial progress, which has been highly acknowledged internationally. In 2011, Germany almost reached the three-percent target for national R&D intensity. Research and innovation of German companies contributed significantly to the stabilisation of the German labour market and to Germany's continuing export success. Science organisations and tertiary education institutions are benefitting from the measures implemented in recent years. To stay on this road to success, Germany will have to strengthen research and innovation also in the future. Yet there are not only successes to be recorded. Not all of the objectives for the ongoing legislative period have been met: although the introduction of R&D tax credits and improved conditions for venture capital had been enshrined in the Federal Government's coalition agreement, these measures have not been implemented. Besides this, there are pressing political tasks relating to organising cooperation between the Federal and state governments (Länder), as well as pressing issues in other policy areas.
Keywords: 330